COST PRINCIPLES IN TERMINATION SETTLEMENTS. - Nelson, Oscar S. (The Accounting Review, 1944)
Abstract Accounting is involved in practically every stage of termination. This must necessarily be so, since accounting is the science of income determination and capital valuation. Whenever profits or values are involved accounting is a must. In termination settlements, the government has adopted a liberal and practical attitude. Accounting principles need not always be rigidly applied in the final settlement. Cost principles governing termination settlements are not applied in the same manner as in settling claims under cost-plus-fixed-fee contracts or facilities contracts. The settlements are more liberal. Furthermore, termination settlements are not complicated like income tax and renegotiation. It is the desire of the government in the U.S. that war contractors, receive speedy and equitable final settlement of claims under terminated war contracts. This desire is expressed by the U.S. Congress in the Contract Settlement Act of 1944 which became effective on July 21, 1944. Provisions in the Act indicate the determination of the government to be fair and square in the settlement of terminated war contracts.